Causal effect of gut microbiota of Defluviitaleaceae on the clinical pathway of “Influenza–Subacute Thyroiditis–Hypothyroidism” - Zhang, Xin; Li, Pei-Heng; Wang, Dongyue; Li, Hancong; Kong, Xiangyu; Zhang, Gongshuang; Zhao, Yue; Liu, Jiaye; Wu, Wenshuang; Zhang, Yuwei; Li, Zhi-Hui; Luo, Han (Frontiers in Microbiology, 2024)
Introduction Hypothyroidism has been found to be influenced by gut microbiota. However, it remains unclear which a taxon of gut microbiota plays a key role in this function. Identifying the key bacteria affects hypothyroidism and through what mechanism will be helpful for the prevention of hypothyroidism through specific clinical pathways. Materials and methods In Study A, 35 families and 130 genera of gut microbiota are used as exposures, with hypothyroidism as the outcome. The causal effect of the gut microbiota on hypothyroidism is estimated through two-sample Mendelian randomization. Combining the results of the two taxonomical levels, key taxa are selected, which in Study B are investigated for their causal association with multiple generally admitted causes of hypothyroidism and their more upstream factors. For validating and revealing the potential mechanism, enrichment analyses of the related genes and interacting transcription factors were performed. Results In Study A, Defluviitaleaceae (OR: 0.043, 95% CI: 0.005–0.363, P = 0.018)/Defluviitaleaceae_UCG_011 (OR: 0.385, 95% CI: 0.172–0.865, P = 0.021) are significantly causally associated with hypothyroidism at both taxonomical levels. In Study B, Defluviitaleaceae family and Defluviitaleaceae_UCG_011 genus show the causal association with decreased thyroiditis (Family: OR: 0.174, 95% CI: 0.046–0.653, P = 0.029; Genus: OR: 0.139, 95% CI: 0.029–0.664, P = 0.043), decreased subacute thyroiditis (Family: OR: 0.028, 95% CI: 0.004–0.213, P = 0.007; Genus: OR: 0.018, 95% CI: 0.002–0.194, P = 0.013), decreased influenza (Family: OR: 0.818, 95% CI: 0.676–0.989, P = 0.038; Genus: OR: 0.792, 95% CI: 0.644–0.974, P = 0.027), and increased anti-influenza H3N2 IgG levels (Family: OR: 1.934, 95% CI: 1.123–3.332, P = 0.017; Genus: OR: 1.675, 95% CI: 0.953–2.943, P = 0.073). The results of the enrichment analysis are consistent with the findings and the suggested possible mechanisms. Conclusion Defluviitaleaceae of the gut microbiota displays the probability of causally inhibiting the clinical pathway of “Influenza–Subacute Thyroiditis–Hypothyroidism” and acts as the potential probiotics to prevent influenza, subacute thyroiditis, and hypothyroidism.